Identification of clinical and radiographic predictors of central nervous system injury in genetic skeletal disorders - Antônio L Cunha (Nature Portfolio, 2021)
Abstract Some studies report neurological lesions in patients with genetic skeletal disorders (GSDs). However, none of them describe the frequency of neurological lesions in a large sample of patients or investigate the associations between clinical and/or radiological central nervous system (CNS) injury and clinical, anthropometric and imaging parameters. The project was approved by the institution’s ethics committee (CAAE 49433215.5.0000.0022). In this cross-sectional observational analysis study, 272 patients aged four or more years with clinically and radiologically confirmed GSDs were prospectively included. Genetic testing confirmed the diagnosis in the FGFR3 chondrodysplasias group. All patients underwent blinded and independent clinical, anthropometric and neuroaxis imaging evaluations. Information on the presence of headache, neuropsychomotor development (NPMD), low back pain, joint deformity, ligament laxity and lower limb discrepancy was collected. Imaging abnormalities of the axial skeleton and CNS were investigated by whole spine digital radiography, craniocervical junction CT and brain and spine MRI. The diagnostic criteria for CNS injury were abnormal clinical and/or radiographic examination of the CNS. Brain injury included malacia, encephalopathies and malformation. Spinal cord injury included malacia, hydrosyringomyelia and spinal cord injury without radiographic abnormalities. CNS injury was diagnosed in more than 25% of GSD patients. Spinal cord injury was found in 21.7% of patients, and brain injury was found in 5.9%. The presence of low back pain, os odontoideum and abnormal NPMD remained independently associated with CNS injury in the multivariable analysis. Early identification of these abnormalities may have some role in preventing compressive CNS injury, which is a priority in GSD patients.